Risk of ozone exposure-induced fracture - Lu, Shuai; Xu, Rongrong; Gong, Maoqi; Zha, Yejun; Li, Ning; Chen, Jia; Liu, Xuejiao; Jiang, Xieyuan (Frontiers in Public Health, 2023)
Ozone (O3) concentrations have been rising yearly while fracture morbidity has also been increasing. Oxidative damage has been implicated as a causative factor for diminished bone mineral density. O3 is known to induce oxidative damage. Nevertheless, few studies have investigated the association between O3 exposure and fractures. Considering the equal growth trends of O3 concentrations and fracture morbidity, in the present study, we aimed to examine whether O3 exposure is associated with the fracture morbidity. Using a retrospective cohort study design, we analyzed the records of 8075 patients with fracture admitted in the warm season to Beijing Jishuitan Hospital from 2014 to 2019 and matched them to the respective time exposure concentration of O3. The results showed that increased odds of fracture were associated with increased O3 concentrations. Therefore, the findings of this study suggest that O3 exposure is a risk factor for fractures, which adds the new evidence of the adverse health effects induced by air pollution. We can conclude that more intensive air pollution control is needed for the prevention of fracture occurrence.